Fiscal and other macroeconomic effects of privatization - Yannis Katsoulakos; Elissavet Likoyanni (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper contains an econometric analysis using country level panel data of 23 OECD countries for the period 1990 - 2000, extending existing empirical work, and more specifically work on the impact of privatization on public deficit, the impact on public debt and the impact on other macroeconomic variables (unemployment and growth). The main results are the following: (i) Recent empirical work (by Jeronimo et al.) using data from 1990-1997 had examined whether privatization receipts have been used as a means of reducing government deficit in Spain, Greece, Italy and Portugal. Their results indicate that there is a negative and statistically significant relationship between receipts from privatization and deficit for the 1990 - 97 period for the four southern countries. Our results with an extended data set show that privatization receipts are not significantly correlated with budget deficit neither for the whole OECD sample, nor for the four southern countries. (ii) We also find that there exists a statistically significant and negative relation between privatization receipts and public debt for the whole OECD sample, while this does not seem to be the case for the three countries with the higher debt over GDP rates (Belgium, Greece and Italy). (iii) One of the most interesting results of our analysis is that current privatization receipts have a statistically significant and negative effect on the current unemployment rate and a positive effect on the previous period's unemployment rate. Intuitively this can be explained by noting that when privatization is announced the accompanied restructuring, which leads firms to operate more efficiently, can cause job losses, and, thus, increase the unemployment rate. On the other hand, when privatization is implemented, new entry in the market occurs, increasing the demand for labor and, thus, decreasing the unemployment rate.
Keywords: H62; H63; J64; L33; 330; Privatization; public deficit; public debt; unemployment; Privatisierung; Öffentliche Schulden; OECD-Staaten; Makroökonomischer Einfluss